Emotion Regulation Difficulties, Personality Traits and Coping Styles in First-Time Suicide Attempters - Özdemir Pinar Güzel; Kefeli, Mehmet Celal; Özcan, Halil (Journal of Psychology and Psychotherapy Research, 2017)
This study examines personality traits, difficulties in emotion regulation and coping styles who presented after the first-time suicide attempt. This study included 54 patients who had attempted suicide and 36 healthy individuals. Suicidal Intent Scale, Beck Depression Inventory, Difficulties in Emotion Regulation Scale, Big Five Inventory and Coping Inventory for Stressful Situations-Short Form used. The suicide attempters had significantly lower scores for extroversion and higher scores for neurosis and higher scores in all the subscales of Difficulties in Emotion Regulation Scale than non-attempters. Emotion-oriented coping scores were significantly higher among suicide attempters while the task-oriented coping and avoidance-oriented scores were significantly higher among the controls. Interventions related to regulation of emotion and problem-solving training may be effective methods for preventing suicide.